Comparative assessment of PM2.5 pollution in Uzbekistan and international air quality standards - Abdullajanov , Botir; Kholmatov, Muhammadyusuf; Ergashkhojayeva , Sabohat; Tursunov, Ahror; Shodmanov, Jasur (Ecological Questions, 2026)
This study evaluates fine particulate matter (PM2.5) pollution in Uzbekistan’s major urban centers, with a particular focus on Tashkent. Real-time monitoring data from the U.S. Embassy air quality station (2020–2025) and national environmental statistics were analyzed to determine compliance with international guidelines. The results indicate that annual average PM2.5 concentrations substantially exceed the World Health Organization (WHO) limit of 5 µg/m³, reaching 52.3 µg/m³ in Tashkent during 2024, and similarly elevated values in Olmaliq (44.0 µg/m³) and Navoiy (38.5 µg/m³). Seasonal variation shows critical wintertime peaks associated with domestic heating, traffic emissions, and weak atmospheric circulation. A comparative assessment reveals that Uzbekistan’s national standards (35–50 µg/m³) remain far more lenient than WHO, U.S. EPA, and EU regulations. This work is the first systematic analysis contextualizing Uzbekistan’s PM2.5 data against global benchmarks. The findings underscore the urgent need for aligning national regulations with international standards, expanding real-time monitoring networks, and implementing targeted policy measures to protect public health.